Alguém ai sabe fazer
a) (m+3)x(m-2)-2(4-m)
b)6-(3+n)+9-6n
c)3b(4-b)-(4+b)
Soluções para a tarefa
Respondido por
2
a) (m+3) x (m-2) - 2(4-m) → m² - 2m + 3m - 6 - 8 - 2m → m² - m - 14 = 0
∆ = (-1)² - 4 × 1 × (-14) → ∆ = 1 + 56 → ∆ = 57
c) 3b(4-b) - (4+b) → 12b - 3b² - 4 + b → -3b² + 13b - 4 = 0
∆ = 13² - 4 × (-3) × (-4) → ∆ = 169 - 48 → ∆ = 121
x = -13 ± √121 → x = -13 ± 11
2 × (-3) -6
x¹ = -13 + 11 → x¹ = -2 ÷2 → x¹ = -1
-6 -6 ÷2 -3
x¹¹ = -13 - 11 → x¹¹ = -14 ÷2 → x¹¹ = -7
-6 -6 ÷2 -3
Espero ter ajudado!!!
andrechaves2003:
Vlwwww mesmoooo❤️
Perguntas interessantes
Química,
10 meses atrás
Matemática,
10 meses atrás
Geografia,
10 meses atrás
Português,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás